Accreditation in Echocardiography: The time to act is now - Herbs, Philip G. (SA Heart Journal, 2017)
Accreditation in echocardiography is an important and necessary next step towards raising standards in the practice of all forms of echocardiography in South Africa. A process of planning and in some cases implementing accreditation amongst the various disciplines performing echocardiography in South Africa is now underway but in widely varying stages of progress. Is our discipline leading the way or have we fallen behind?.